ANALISIS PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PARTISIPASI KERJA PENDUDUK LANJUT USIA DI KABUPATEN BADUNG - Ni Putu Kirey Sari Cahyani; Made Dwi Setyadhi Mustika (E-Jurnal Ekonomi Pembangunan, 2023)
The high level of employment of the elderly population indicates that the contribution of the elderly to the economy is quite large, both to meet their own needs and to take care of family dependents. The purpose of this study was to analyze the effect of age, marital status, residence status, education, non-labor income, work dependents and health on the work participation of the elderly in Badung Regency. The collected data were then analyzed using descriptive analysis, multiple linear regression and the classical assumption test. The results showed that age, marital status, residence status, education, non-labor income, family dependents and health simultaneously affect the work participation of the elderly in Badung Regency. Age and non-labor income partially have a positive and significant effect on the work participation of the elderly in Badung Regency, while education, marital status, residence status partially have a negative effect on the work participation of the elderly in Badung Regency. Family dependents and health variables have no significant effect on the work participation of the elderly in Badung Regency. The implication of this research is in line with Borjas' theory of neoclassical capital of labor or leisure choice, namely the neoclassical capital of work life which concerns an individual's choice to work or enjoy leisure time, which can be expressed as individual satisfaction with consumption and leisure time enjoyment.